The Construction of Hierarchical Command Centers - Ni Ming; He Xiang; Zhang Wei; Ge Xin; Liu Huan; Wang Jun; Liu Shijin (SHS Web of Conferences)
The construction of hierarchical command centers realizes that in the process of emergency command development, each command center needs to operate independently, each level has different working conditions, and each level has different concerns. It is the independent work setting of emergency command centers at all levels. The collection of working environments can effectively empower the construction of a new generation of emergency command systems.